The Role of PV-Integrated Double-Skin Facades in Achieving Net-Zero Carbon Emissions in Commercial Buildings in Morocco - Idouanaou Abdessamad; Malha Mustapha; Bah Abdellah; Ansari Omar (EPJ Web of Conferences)
The construction and operation of commercial buildings significantly contribute to global greenhouse gas emissions. This study investigates the effectiveness of photovoltaic (PV)-integrated double-skin facades (DSFs) in reducing operational energy use and carbon emissions in Moroccan commercial buildings. Using dynamic energy simulations, various DSF glazing configurations were analyzed for their impact on heating and cooling energy demand, electricity consumption, and CO2 emissions. The results reveal that PV-integrated triple glazing reduces cooling energy demand by nearly 10% and decreases total electricity consumption by about 5% annually. Compared to single glazing, this configuration achieves an additional 2.85% reduction in CO₂ emissions. Despite minor differences in solar energy conversion efficiency, the system maintains high levels of on-site renewable energy generation. These findings highlight the potential of PV-DSF systems to support Morocco’s net-zero carbon goals by enhancing building energy performance. However, seasonal variations in performance suggest the need for energy storage integration to achieve year-round carbon neutrality. The study recommends further research focusing on experimental validation and the large-scale implementation potential of PV-DSF solutions in the commercial building sector.